2022
DOI: 10.1126/sciadv.abm6063
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum chaperone genes encode effectors of long-term memory

Abstract: The mechanisms underlying memory loss associated with Alzheimer’s disease and related dementias (ADRD) remain unclear, and no effective treatments exist. Fundamental studies have shown that a set of transcriptional regulatory proteins of the nuclear receptor 4a (Nr4a) family serve as molecular switches for long-term memory. Here, we show that Nr4a proteins regulate the transcription of genes encoding chaperones that localize to the endoplasmic reticulum (ER). These chaperones fold and traffic plasticity-relate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…Next, we asked whether our model could identify spatial signatures of learning in brain slices of mice following spatial object recognition (SOR) training, a widely used behavioral paradigm to investigate memory mechanisms 24 . Using spatial transcriptomic data from brain slices of SOR-trained and homecage control (HC) mice, we applied our model to predict activity for each spot and clustered all spots into anatomical regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we asked whether our model could identify spatial signatures of learning in brain slices of mice following spatial object recognition (SOR) training, a widely used behavioral paradigm to investigate memory mechanisms 24 . Using spatial transcriptomic data from brain slices of SOR-trained and homecage control (HC) mice, we applied our model to predict activity for each spot and clustered all spots into anatomical regions.…”
Section: Resultsmentioning
confidence: 99%
“…The dataset contains spatial RNA-sequencing of whole brain slices from 1 hour after SOR training or home cage controls. SOR training was performed as previously described 24 . Mouse brain section per mouse was cut at 10 µm thickness and mounted onto each Visium slide capture area.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of neurodegenerative diseases, a DnaJ domain-containing protein Droj2 has been suggested to be a negative regulator of memory in the Drosophila model of Alzheimer's disease (Ring et al, 2022). ER chaperones Hspa5 and small heat shock protein 22 (sHsp22) were found to improve the impairment in spatial learning and memory deficit in a mice Tauopathy model (Chatterjee et al, 2022;Rodriguez Ospina et al, 2022). Through our work we implicate the chaperone Mrj, to play a crucial role in the regulation of long-term memory in a non-stressed and non-disease condition.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate transcription factors (TFs) within the PWS-ER chaperone GRN are those with binding site motifs enriched in the promoters of DEGs in PWS β-cells, including, but not limited to the known ATF6 co-factor NFYA, which has roles in insulin secretion and glucose homeostasis [90], as well as PPARB/D also with known roles in β-cell mass and insulin secretion [91]. Intriguingly, a recently published study found that TFs of the nuclear receptor 4A (NR4A) family that participate in long-term memory in mice act through coordinate regulation of numerous ER chaperones [92], with a high degree of concordance with the dysregulated ER chaperones that we identified in PWS INS-1 cell lines; nevertheless, NR4A pathway factors are not DEGs in PWS β-cells.…”
Section: Discussionmentioning
confidence: 99%